2017
DOI: 10.21315/mjms2017.24.5.1
|View full text |Cite
|
Sign up to set email alerts
|

The Future Hospital: A Business Architecture View

Abstract: The future hospital is a resilient, physical learning facility featuring digital enhancement and leveraging an ecosystem of platforms for the Internet of Things (IoT) and analytics, achieving patient-centric care delivery via multidisciplinary healthcare provider teams coordinated to meet patients' medical, psychological, social and economic needs. It exists in a just ecosystem that assimilates the care spectrum from healthy living, the prevention of disease to acute care and the rehabilitation of patients rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…The findings of the present study on the roles and mission of future hospitals indicated that the construction of hospitals would be different in the future, and hospitals would be built with newer standards and different from current hospitals. [ 13 14 ] According to the type of standards in future hospitals, they would be designed in a way that the population covered by them would be certain, and services would be provided and supervised more professionally by state centers and lower levels of the health system structure. [ 13 14 15 ] By defining the population covered by hospitals, it seems that the responsibility for health and services will be borne by those hospitals and they will focus on the health orientation.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the present study on the roles and mission of future hospitals indicated that the construction of hospitals would be different in the future, and hospitals would be built with newer standards and different from current hospitals. [ 13 14 ] According to the type of standards in future hospitals, they would be designed in a way that the population covered by them would be certain, and services would be provided and supervised more professionally by state centers and lower levels of the health system structure. [ 13 14 15 ] By defining the population covered by hospitals, it seems that the responsibility for health and services will be borne by those hospitals and they will focus on the health orientation.…”
Section: Discussionmentioning
confidence: 99%
“…AI can also make a contribution to diagnostic procedures by doctors 2 (see Amato et al 3 for a general overview of AI for medical diagnoses). The idea of a ‘smart’ hospital, with programs and devices coordinated by AI, is no longer just science fiction 4 . AI also has roles to play in identifying drug interactions, interpreting possibly minute details in images, logging and processing health records, and more.…”
Section: Introductionmentioning
confidence: 99%
“…The idea of a 'smart' hospital, with programs and devices coordinated by AI, is no longer just science fiction. 4 AI also has roles to play in identifying drug interactions, interpreting possibly minute details in images, logging and processing health records, and more. Still, rigorous research into the performance of AI in many of these areas is still in its infancy.…”
mentioning
confidence: 99%
“…Studies show that lack of proper management and management capability in health care organization lead to not achieved goals in the health sector. Therefore, all efforts to improve the implementation of policies in the health sector have not delivered or have been followed slowly (10). Another study revealed that we should use adaptable and flexible managers and effective leaders to deal with the current challenges in the health care sector.…”
Section: Introductionmentioning
confidence: 99%